COLOR’S DELIGHTFUL PORTRAYAL OF THE MELODY OF THE MUSIC BY COLOR: संगीत की राग-रागिनियो का रंगो द्वारा मनभावन चित्रण - Verma, Vinita (International Journal of Research -GRANTHAALAYAH, 2014)
That is to say, the vision of different arts, acting Angopag etc. together form a parametra. Because music is the most subtle and emotional feature of all the arts. For example, playing vocal properties or musical instruments in such a way that in terms of proportion, balance harmony, tone, rhythm, the fine vocal combination and melody of a raga-ragini is expressed with the right intensity, volume and variety. Due to the beauty, beauty and liveliness, the painting has been written with special grace and superior than other arts. अर्थात् विभिन्न कलाओं की दृष्टि, अभिनय अंगोपाग आदि मिलकर एक परमचित्र का निर्माण करते हैं। क्योंकि सभी कलाओं में संगीत ही सबसे अधिक सूक्ष्म एवं भावप्रधान विशेषताओं से अंलकृत हैं। जैसे स्वर के गुण अथवा वाद्य यंत्रो को इस प्रकार बजाना कि अनुपात, संतुलन समरसता आलाप, तान लय ताल की दृष्टि से किसी राग-रागिनी का बारीक स्वर संयोजन और सुरीलापन ठीक प्रबलता, मात्रा और वैविध्य के साथ अभिव्यक्त हो जाये।साथ ही अपने ओज माधुर्य सौन्दर्य तथा सजीवता के कारण चित्रकला को विशेष शोभामय तथा अन्य कलाओ की तुलना में श्रेष्ठ मानकर लिखा गया है